Remote climate change propagation across the oceans—the directional swell signature. (14th June 2021) - Lemos, Gil; Semedo, Alvaro; Hemer, Mark; Menendez, Melisa; Miranda, Pedro M A
Abstract: The energy content of wind-waves is propagated across the oceans in the form of swell waves, the main drivers of long-term changes in coastal morphology and offshore hazards. A state-of-the-art swell tracking algorithm is applied to a global ensemble of CMIP5 dynamic wave climate projections, to assess future changes in remotely originated swell events towards the end of the 21st century, and how they propagate. The contribution of multiple wave generation areas is considered. It is found that the projected climate change signal is effectively propagated from the winds along the extratropical storm tracks to remote locations, in the tropical and subtropical latitudes, through swell waves. The statistically significant projected changes in swell wave heights and swell predominance at the remote swell arrival locations are comparable with the ones at the wave generation areas. Furthermore, different incoming directions for swell events at remote locations are shown to often carry opposite climate change signals, propagated from different remote origins. These results highlight the need for a directional approach on wave climate projections, critical for improved vulnerability assessments and adaptation measures from the climate community.